Commuting: Who pays the bill? Overview of fiscal regimes for commuting in Europe and recommendations for establishing a level playing-field. - Haubold, Holger (My University, 2014)
Commuting stands for an important share of traffic in Europe. Numerous studies have shown that commuting by active modes of transport like cycling or walking has major benefits - a small impact on the environment, less use of public space than for motorised transport, and various positive health effects. Nevertheless, favourable tax treatment for active modes of transport like cycling exists only in a few countries, most notably Belgium or the United Kingdom. Other countries, like France, are currently exploring possibilities to introduce instruments like a cycling mileage allowance for commuting. Accompanying studies show that these instruments would be cost-efficient for public budgets - for example, the proposed cycling allowance in France would have a cost of 0.075 billion for public budgets, whereas tax subsidies for company cars lead to direct government revenue losses of 54 billion in the EU according to a paper published by the European Commission. While some studies have compared different company car tax regimes in Europe, so far no comparison has been made on how tax systems treat other modes of transport for commuting, such as cycling or public transport. Using input from its Member Organisations and its National Cycling Officer network, ECF has therefore conducted a study comparing different fiscal regimes for commuting by cycling, public transport and car in 11 European countries chosen according to the availability of data. This was done with a view to identify best practices for incentivising sustainable ways of commuting, like the cycling mileage allowance for home-work travel that exists in Belgium or tax exemptions for the provision of bikes by companies to their employees that exist in the United Kingdom and in the Netherlands. This study gives general as well as country-specific policy advice to decision-makers at the European and the national level on how to create a level playing field for all modes of transport throughout Europe, including those - like cycling - which have a positive impact on the environment and public health. In order for this levelling to be achieved, incentives for active and environmentally friendly modes of transport like cycling should be introduced - or extended where they already exist. It should be possible to combine these incentives with those for the use of public transport in order to support intermodality. At the same time, environmentally harmful tax subsidies for e.g. company cars need to be replaced by mode-neutral solutions like mobility budgets in all EU Member States.
Keywords: Individualverkehr; Fahrradverkehr; Pendlerverkehr; Stadtverkehr; Arbeitsmigration; Steuer; Arbeitsplatz; Arbeit; Handlungsempfehlung